Urethral duplication—Epidemiology, diagnosis, and treatment in a case series of 19 patients. Issue 3 (June 2020) - Guglielmetti, Laura Chiara; Delcont, Mellissa; Walker, Jonathan; Wilcox, Duncan; Vuille-dit-Bille, Raphael N.
Summary: Background: Urethral duplications are rare congenital anomalies of the urinary tract. Because of their rare occurrence, evidence about epidemiology, diagnosis and treatment is limited. Objective: The aim of this study was to describe the characteristics, presentation, and treatment of a single large cohort of patients. Study design: The authors describe a cohort of 19 consecutive patients with urethral duplications treated at a single referral institution over a 15-year period. Type of duplication, comorbidities, diagnosis, and treatments are described. Results: 68% of the patients were male, and the age at diagnosis ranged from 0 days to 120 months. The most common type of urethral duplication in this cohort of patients was IIA-2 according to Effmann (26%). Diagnosis was made by healthcare providers in 90% and by the children's mothers in 10% of the patients. Furthermore, 10% of patients presented with urinary tract infections. Only 26% of the patients did not have associated diseases or disorders. Fifteen (79%) patients were treated surgically, with a mean number of 2 (standard deviation 1.6) surgeries per patient. Surgeries were performed ranging between 2 days and 10 years of age. Discussion: The authors report one of the largest cohorts of patients with urethral duplication. There was a male preponderance, urinary tract infections were rare, and most patients had associated disorders, which is in line with previous reports. In this cohort, most duplications were discovered by healthcare providers, and a small number of patients did not undergo surgical treatment. The broad spectrum of duplications could be confirmed with type IIA-2 being the most common type. The mean number of two procedures per patient was low compared with previous reports. Image 1